Combined QTL-Seq and Traditional Linkage Analysis to Identify Candidate Genes for Purple Skin of Radish Fleshy Taproots - Liu, Tongjin; Wang, Jinglei; Wu, Chunhui; Zhang, Youjun; Zhang, Xiaohui; Li, Xiaoman; Wang, Haiping; Song, Jiangping; Li, Xixiang (Frontiers in Genetics, 2019)
Taproot skin color is a crucial visual and nutritional quality trait of radish, and purple skin is most attractive to consumers. However, the genetic mechanism underlying this character is unknown. Herein, F2 segregating populations were constructed to investigate radish genomic regions with purple skin genes. Segregation analysis suggested that pigment presence was controlled by one dominant gene, Rsps. A bulk segregant approach coupled to whole-genome sequencing (QTL-seq) and classical linkage mapping narrowed the Rsps location to a 238.51-kb region containing 18 genes. A gene in this region, designated RsMYB1.1 (an Arabidopsis PAP1 homolog), was a likely candidate gene because semiquantitative RT-PCR and quantitative real-time PCR revealed RsMYB1.1 expression in only purple-skinned genotypes, sequence variation was found between white- and purple-skinned radishes, and an InDel marker in this gene correctly predicted taproot skin color. Furthermore, four RsMYB1.1 homologs (RsMYB1.1-1.4) were found in ‘XYB36-2’ radish.RsMYB1.1 and the previously mapped and cloned RsMYB1.4 (contributing to red skin) were located on different chromosomes and in different subclades of a phylogenetic tree; thus, they are different genes. These findings provide insight into the complex anthocyanin biosynthesis regulation in radish and information for molecular breeding to improve the anthocyanin content and appearance of radish taproots.